Democracy, Backsliding, and Catholicism - Himes, Kenneth R. (Theological studies, 2026)
The state of democracy is declining worldwide, and that includes the United States, the oldest constitutional democracy. Various scholars have proposed theories regarding the growth and decline of democracy in the twenty-first century. Many commentaries point to a new threat to democracy that goes by a variety of names. This essay aims to understand the cause of the democratic decline and the Catholic Church?s role in supporting democracy.